The Influence of The Role And Performance of Farmers' Groups on The Productivity of Corn Farming In Karangasem Village, Wonorejo District Pasuruan Regency - Aji, Teguh Sarwo; Wahyuni, Siti (Journal of Economic, Management and Entrepreneurship, 2025)
Low farmer participation in farmer groups poses a challenge to increasing farm productivity at the village level. This study aims to examine the influence of the role and performance of farmer groups on corn farming productivity in Karangasem Village, Wonorejo District, Pasuruan Regency. The role of farmer groups is assessed using five indicators: their function as learning classes, collaboration platforms, production and economic units, information channels, and institutional strengthening. Farmer group performance is measured through member participation, administration, activity planning, external cooperation, and achievement of group goals. This study used a quantitative approach with a survey method of 82 respondents who were active members of four farmer groups. Data analysis was conducted using multiple linear regression with classical assumption testing. The results show that, both partially and simultaneously, the role and performance of farmer groups have a positive and significant effect on corn farming productivity. The coefficient of determination (R²) value of 0.624 indicates that 62.4% of the variation in productivity can be explained by these two variables. This finding emphasizes the importance of strengthening farmer group institutions in supporting production increases. The study recommends ongoing interventions through technical assistance, farmer capacity building, and further studies with other variables such as access to capital, technology, and agro-climatic factors